Saturated Magnetization in Sm and Tb Doped La(Fe0.88Si0.12)13 - Vuong, Van Hiep (H. : ĐHQGHN, 2019)
The saturated magnetization in 20% substituted La0.8R0.2(Fe0.88Si0.12)13 (R = Sm, Tb) magneto-caloric alloys is discussed in this work. The measurements were taken up to 70 kOe (7 Tesla) to detect the saturation of magnetic moments. As reported recently [Mat. Trans. 59(7) (2018) 1068], these compounds show a large variation of magnetic entropies at low field variation (~ 1.5 T), which associate with the large relative cooling efficiency (RCP) of 52 (for Tb-doped) and 102 J/kg (for Sm-doped) even at low effective DH of ~ 15 kOe. We re-detected the effective range of field variation DH and recognized that the effective DH ~ 5 kOe which is much lower than the value of other magneto-caloric compounds and is excellent for application of Sm-doped compound in modern cooling devices.